Oral levofloxacin: population pharmacokinetics model and pharmacodynamics study in bone and joint infections. (18th February 2022) - Canouï, Etienne; Kerneis, Solen; Morand, Philippe; Enser, Maya; Gauzit, Rémy; Eyrolle, Luc; Leclerc, Philippe; Contejean, Adrien; Zheng, Yi; Anract, Philippe; Hirt, Deborah; Treluyer, Jean Marc; et al.
Abstract: Objectives: This study aimed at characterizing the pharmacokinetics (PK) of oral levofloxacin in adult patients in order to optimize dosing scheme and explore the PK/pharmacodynamics (PD) of levofloxacin in bone and joint infections (BJIs). Methods: From November 2015 to December 2019, all patients hospitalized in Cochin Hospital, treated with levofloxacin and who had at least one dosage for therapeutic drug monitoring were included. PK was described using non-linear mixed-effect modelling. In a subgroup of patients with BJIs, the association between PK, MIC for the isolated pathogen and clinical outcome was investigated. Monte Carlo simulations investigated dosing regimens to achieve the PK/PD target (AUC/MIC ratio >100). Results: One hundred and two patients were included (199 measurements), including 32 treated for BJI. A one-compartment model with first-order absorption and elimination best described the data. Effects of estimated creatinine clearance (eCLCR ) and age were significant on levofloxacin clearance. In BJI patients, no significant association was found between levofloxacin PK/microbiological parameters and either clinical outcome or adverse events. Based on our model, we proposed optimized oral levofloxacin dosing regimens according to renal function, to reach the PK/PD target AUC/MIC ratio >100 for three frequent causative pathogens ( Staphylococcus aureus, Enterobacterales and Pseudomonas aeruginosa ). Conclusions: Our results reinforce the need of determining the MIC and using therapeutic drug monitoring in complex infections caused by P. aeruginosa .